Knowledge transfer, macro stickiness and human capital development among technology-based firms in Malaysia - Mhd. Sarif, Suhaimi (2011)
The study investigates the presence of macro stickiness in knowledge transfer for human capital development among technology-based firms in Malaysia. Macro stickiness refers to vague and inadequate guidance for knowledge transfer for innovation and knowledge development promoted by national policies on innovation and economy. The study used personal interview with twenty (20) informants, who included two (2) policy makers, three (3) government officers, and fifteen (15) executives of technology-based firms in selected Malaysian technology parks. The findings suggest that policy makers and government officers confirmed that national policies on innovation and economy cannot exclude three national unity, foreign direct investment and sound economic growth. The industry informants were not convinced to active in knowledge transfer for human capital development due to the inclusion of three elements. The study proposed that future research to increase the number of interviewees and to include technology parks from other major cities.